Investigating the fitness benefit of reverse transcriptase (RT) mutation A62V when co-occurring with M184V and K65R in HIV-1 subtype C - Njenda, Duncan Tazvinzwa (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.